Sistem Pemerintahan Tradisional di Kampung Adat Cirendeu: Antara Kearifan Lokal dan Tantangan Modernisasi - Andre, Andre; Rahman, Hilmi Julia Saiful; Pamungkas, Akmal Catur; Jamil, Astri; Dimyati, Endang (Journal of Multidisciplinary Inquiry in Science, Technology and Educational Research, 2025)
Kampung Adat Cirendeu is one of several indigenous communities that continue to uphold local traditions amidst the pressures of modernization. This study aims to understand the traditional governance structure in Kampung Adat Cirendeu, the local wisdom values it embodies, and how this community confronts the challenges of modernization. Data were collected through extensive interviews with traditional leaders and village administrators. The findings indicate that the traditional governance structure comprises the Sesepuh (Elders), Ais Pangampih, Paniten, and several other officials, each with specific duties. The Cirendeu indigenous community employs selective adaptation strategies to preserve their local wisdom, even though modernization brings government programs that sometimes conflict with their customs. This study provides insights into how local traditions can endure in the face of changing times.